Three-Input One-Output Voltage-Mode Biquadratic Filter Using Single VDBA - Roongmuanpha, Natchanai; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2020)
In this article, a voltage-mode universal biquadratic filter with triple inputs and single output (TISO) is presented. The circuit consists of only one voltage differencing buffered amplifier (VDBA) along with two capacitors and one resistor. The proposed circuit can realize all five standard biquadratic filter functions namely, lowpass (LP), highpass (HP), bandpass (BP), bandstop (BS) and allpass (AP) without disturbing the circuit structure. The quality factor (Q) and the natural angular frequency (ωo) of the proposed circuit can be controlled by means of the transconductance gain of the VDBA. The circuit also provides low sensitivity performance. The potentiality of the proposed TISO biquadratic filter has been proved by PSPICE program based on TSMC 0.25-μm CMOS technology.
Keywords: biquadratic filter; electronically tunable; Voltage Differencing Buffered Amplifier (VDBA); voltage-mode circuit